IMAGE AND MEMORY: OEDIPUS AND THE THEATER SCENE OF PORTO ALEGRE. - Silva, Newton Pinto da (2012)
This paper investigates the theater scene of Porto Alegre in 1980. In particular, we make an analysis of the play The True Story of Oedipus (Group Greeks and Trojans), in an attempt to reconstruct it through their traces. The main research paper is a video, made by TVE / RS, which recorded this play for viewing on a television broadcaster.